PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KOMPENSASI TERHADAP KEPUASAN KERJA GURU SMPN KOTA SEMARANG - Sudharto . (LPMPP Universitas Negeri Yogyakarta, 2011)
Abstract: The Contributions of Principals’ Leadership and Compensation to the Job Satisfaction of State Junior High School Teachers in Semarang. The objective of the study is to investigate the contributions of principals’ leadership and compensation to teachers’ job satisfaction. The sample consisted of 288 teachers of state junior high schools in Semarang. The data were collected using a questionnaire and were analyzed using a regression technique. The results show that: (1) individually and aggregately, there are positive and significant contributions of principals’ leadership and compensation to teachers’ job satisfaction; and (2) 45.7% of teachers’ job satisfaction is contributed by principals’ leadership and 30.1% by compensation. It can be concluded that principals’ leadership has a greater contribution than compensation to the improvement of the satisfaction of teachers of state junior high schools in Semarang. Keywords: principals’ leadership, compensation, teachers’ job satisfaction